Eworklife: developing effective strategies for remote working during the COVID-19 pandemic - Rudnicka, Anna; Newbold, Joseph W.; Cook, Dave; Cecchinato, Marta E.; Gould, Sandy J.J.; Cox, Anna L. (2020)
ABSTRACT The COVID-19 pandemic means governments have advised citizens to engage in “social distancing” measures, which include working from home. Many people have had to learn how to work from home and develop effective strategies in a very short period. This especially rapid move to remote working is unprecedented, so we do not know how this shift is affecting people’s working lives. We developed a mixed-methods survey and a series of in-depth interviews, through which we investigated the new challenges for people in managing digital self-control, maintaining productivity and work-life balance that have surfaced during the COVID-19 crisis. We also catalogued the strategies participants adopted through the first stages of lockdown in response to these challenges. From this, we draw research and policy implications for supporting neophyte remote workers when managing digital self-control, productivity, and work-life balance during and beyond the COVID-19 pandemic. Keywords working from home, work life balance, COVID-19 ABOUT THE AUTHOR/S Anna Rudnicka University College London anna.rudnicka.15@ucl.ac.uk Joseph W. Newbold Northumbria University joseph.newbold@northumbria.ac.uk Dave Cook University College London david.cook.15@ucl.ac.uk Marta E. Cecchinato Northumbria University marta.cecchinato@northumbria.ac.uk Sandy J.J. Gould University of Birmingham s.gould@cs.bham.ac.uk Anna L. Cox University College London anna.cox@ucl.ac.uk E-WORKLIFE was created by researchers in digital distraction and work-life balance to explore evidence-based strategies to support remote working. It builds on a decade of our research into how to best manage our digital devices to support both the work and non-work parts of our lives. The team, led by Prof Anna Cox consists of researchers from UCL, Northumbria University and University of Birmingham. https://www.eworklife.co.uk/team/ New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).